The effect of molecular mass on the polymorphism and crystalline structure of isotactic polypropylene (eXPRESS Polymer Letters, 2010)
This study is devoted to the investigation of the effect of molecular mass on the α-, β- and γ-crystallization tendency of isotactic polypropylene (iPP). The crystalline structure was studied by wide angle X-ray scattering (WAXS) and by polarised light microscopy (PLM). The melting and crystallization characteristics were determined by differential scanning calorimetry (DSC). The results indicate clearly that iPP with low molecular mass crystallizes essentially in α-modification. However, it crystallizes in β-form in the presence of a highly efficient and selective β-nucleating agent. The α- and β-modifications form in wide molecular mass range. The decreasing molecular mass results in increased structural instability in both α- and β-modifications and consequently enhanced inclination to recrystallization during heating. The formation of γ-modification could not be observed, although some literature sources report that γ-form develops in iPP with low molecular mass.